OP72 Creation, validation and evaluation of the Adolescent Diabetes Needs Assessment Tool (ADNAT) App to help young people manage Type I Diabetes: methodological overview. (13th September 2016) - Lancaster, GA; Cooper, H
Abstract : Background: The UK has the fifth largest paediatric diabetes population in the world, but one of the poorest levels of diabetes control. Only 15.8% of young people (YP) with Type I diabetes achieve recommended glycaemic targets, putting the majority at high risk of future complications. We describe a programme of research over an 8 year period to develop a unique tool that concurs with YPs' diabetes lifestyles and integral use of technology set within an educational framework. Methods: Aims: (1) to overview the methodological development of a diabetes needs assessment tool designed to guide the delivery of care and individual needs of YP with Type I diabetes; (2) to demonstrate its reliability and validity; (3) to evaluate how ADNAT can be used effectively in clinical practice as an App. A 5 stage mixed methods approach incorporating identification of a pool of potential items from previous studies (qualitative study, systematic review); selection of items using the Delphi method with experts; systematic item reduction with cognitive interviews, pre-testing, piloting, reliability and validity (n = 155); transference to IT format; followed by a pilot evaluation of its implementation in 3 Paediatric Diabetes Units in NW England (n = 45). Results: The ADNAT APP has been developed, psychometrically tested and evaluated for 12–18 year olds. It consists of 117 questions divided between 6 domains (all about me, physical activity, eating, monitoring blood glucose, medication taking, living with diabetes) with 36 of the questions, hidden amongst the total, providing 2 scored 'Needs Assessment Ratings' relating to self-care and psychosocial health. The tool uses traffic light labelling to highlight problem areas. Face/content validity were positively evaluated, Kappa statistics showed good reliability (0.42–0.82), and tests for validity found significant correlations with SMOD-A (r = 0.41, IC: < 0.001), and HbA1c levels (r = 0.16, IC: = 0.056). Item total polyserial correlations and item response analysis validated the use of simple additive scores (r = 0.87). Evaluation (using the REAIM framework) produced recommendations for successful implementation. Conclusion: The ADNAT App has been developed and tested in collaboration with YP, their carers and health professionals. ADNAT allows the YP to see how their domains and HbA1c inter-relate and impact on their personal diabetes fitness. It combines reflective questioning with needs assessment to raise self-awareness to support adolescent decision making. ADNAT has been included in the National Paediatric Diabetes Improvement Plan for 2013–2018.